EXAMINING THE ROLE OF WATER MANAGEMENT STRATEGIES IN DESERTIFICATION PREVENTION: A COMPREHENSIVE ANALYSIS - Haydarov Hasanjon Hakimovich; Kushimov Bakhtiyor Alishovich (Journals Park Publishing, 2023)
Desertification is a complex environmental issue with far-reaching consequences, posing significant challenges to ecosystems, communities, and sustainable development. Effective water management strategies play a crucial role in mitigating desertification and promoting environmental resilience. This scientific article provides a comprehensive analysis of the topic, exploring the explanation, key concepts, and implications of water management strategies in desertification prevention. The article includes an introduction, literature review, methodology, results, discussion, conclusion, and bibliography to provide a holistic understanding of this critical subject
Keywords: desertification, water management, prevention strategies, ecosystem resilience, sustainable development.